Φωκαϊκά σπαράγματα - Ευθυμιάδης Στέφανος; Μαζαράκης Ανδρέας (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 2008)
The starting point for this publication of miscellaneous materials regarding Phocaea was the discovery of the dossier of the French archaeologist Félix Sartiaux that had been deposited in the French Archeological School in Athens but was so far considered lost. Sartiaux excavated in the area of Phocaea (Western Asia Minor) during the troubled years 1913-1921, a work which, owing to the sad events of the summer of 1922, had to stop and be resumed after the 1950s by the Turkish archaeologists Akurgal and Ozyigit. Sartiaux was primarily interested in the archaic period of the town which was closely associated with the Greek colonisation of the Western Mediterranean, especially the foundation of Marseille. Yet his letters and archeological report published here provide valuable information for later periods of the town as well, among which the Genoese and modern periods. Furthermore, they document the wider interest of French archeologists in claiming the domain of Western Asia Minor for themselves and away from their German counterparts. The publication of Sartiaux’s dossier is supplemented here with specific studies on the medieval history and archeology of the town. Stephanos Efthymiadis discusses all scattered evidence concerning Byzantine Phocaea, when the town, a rather small bishopric, was mostly known as a centre of production of ceramics, textiles, and probably alum, a mineral that was later commercially exploited by the Genoese (end of 13th c.- 15th c.). Its mention in the edict of Alexios I Komnenos that granted privileges to the Venetians (1082) and the attestation of an Amalfitan merchant as its inhabitant in the 12th century show that Phocaea began to acquire a certain economic significance well before its concession by Michael Vili Paleologos to the Genoese family of Zaccaria (ca. 1268). The study of Andreas Mazarakis, “The Zaccaria in Phocaea (ca. 1268-1329),” is concerned with problems of prosopography and the trading activity of this family. Drawing on historiography, numismatics, and Genoese notarial documents, the author discards previous misunderstandings and puts in order all the information regarding the political and other activities of the Zaccaria in the Byzantine or Frankish Levant. His four other studies concern the problems of alum exploitation in Old Phocaea and on the adjacent island of Lesbos; the commemorative slab of the Gattelusi, lords of Mytilene and Old Phocaea, walled in a still standing nineteenth-century house; the anonymous Venetian atlas MGI 1694 of the National Library of Austria, which dates from the year 1656 and features a representation of Old Phocaea; and a note on the property status of land-owners in Phocaea as recorded in the map drawn up by Sartiaux in 1921.